Importance of Angle Correction in the Measurement of Blood Flow Velocity with Transcranial Doppler Sonography - Krejza, Jaroslaw; Mariak, Zenon; Babikian, Viken L. (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: The angle of insonation cannot be assessed with conventional transcranial Doppler sonography. Findings in healthy control subjects suggest that the angle is relatively small in routine clinical practice. Data regarding the angle in middle cerebral artery (MCA) stenosis are scarce. In this study, the angle and its effect on flow velocity measurements were assessed with transcranial color Doppler sonography in patients with MCA stenosis.METHODS: Eighteen patients (median age, 53 y; age range, 22–72 y) who satisfied qualifying criteria (eg, angiographically revealed unilateral MCA stenosis of ≥50%) were selected from 149 consecutive patients enrolled in a prospective study of transcranial color Doppler sonography and cerebral digital subtraction angiography. All had active neurologic symptoms. The angle of insonation and peak systolic and mean flow velocities in both MCAs were measured from videotapes generated at sonography.RESULTS: The mean angle of insonation was 47 ± 11° (range, 19–64°) on the stenotic side and 34 ± 18° on the contralateral side (P < .05). Angle-corrected velocities were higher than uncorrected ones. Differences between angle-corrected and uncorrected peak systolic and mean flow velocities on the stenotic side were 46.6% and 45.9%, respectively, of uncorrected values. Differences between corrected and uncorrected peak systolic and mean velocities were larger on the stenotic side compared with those on the contralateral side (P < .05).CONCLUSION: In patients with moderate or severe MCA stenosis, the angle of insonation can be substantial and cause large errors when flow velocities are measured without angle correction.